DAMPAK SENSE, FEEL, THINK, ACT, RELATE DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN CAFE DI SURABAYA - Lilik Indrawati; Devi Dian Amalia (Politeknik Ubaya, 2020)
ABSTRACT This research was conducted on 150 respondens, through a questionnaire. The analysis used in this study uses the validity test, reliability test, classic assumption test, multiple linear regression test,determinant coefficient, and test. The results of data processing SPSS 22.0, namely: Sense has no effect on customer satisfaction PaperCup Coffee Surabaya because the value of t count < t table (1.030<1.977), then H0 is accepted and H1 is rejected. This means that there is no significant influence between sense and customer satisfaction at PaperCup Coffee Surabaya. Feel does not affect customer satisfaction PaperCup Coffee Surabaya because the value of t arithmetic < t table (0.953< 1.977) then H0 is accepted and H1 is rejected. This means that is no significant influence between feel and customer satisfaction at PaperCup Coffee Surabaya. Think does not affect customer satisfaction PaperCup Coffee Surabaya because the value of t arithmetic <t table ( 1.158 <1.977), then H0 is accepted and H1 is rejected. This means that there is no significant influence between think and customer satisfaction at PaperCup Coffee Surabaya. Act affects customer satisfaction of paperCup Coffee Surabaya because the t value < t table (3.244> 1.977) with a significant level 0f 0.001< 0.050, then H0is rejected and H1 is accepted. This means that there is a significant influence between act and customer satisfaction at PaperCup Coffee Surabaya.Relate to customer satisfaction PaperCup Coffee Surabaya because t count value< t table (2.530> 1.977) with a significant level of 0.012 < 0.050, then H0 is rejected and H1 is accepted.This means that there is a significant influence between relate and customer satisfaction at PaperCup Coffee Surabaya. Brand Image has no effect customer satisfaction PaperCup Coffee Surabaya because the value of t arithmetic <t table (1.942<1.977), then H0 is accepted and H1 is rejected.This means that there is no significant influence between brand image and customer satisfaction at PaperCup Coffee Surabaya.Regression test result of multiple linear effect of the 6 independent variables that have the greatest contribution is act variable (X4) that is 0.328 or 32.8%. The result of the determinant coefficient show and adjusted R square of 0.441 (44.1%, meaning that the independent variables are sense (X1), feel (X2), Think (X3), Act (X4), Relate (X5) and Brand Image (X6) contributes moderately to the dependent variable, Customer Satisfaction (Y). The result of multiple linear regression: Y= 3.078+0.075X1+0.095X2+0.107X3+0.328X4+0.253X5+0.176X6. Based on the results of the study it can be concluded that the results of the adjusted R square of 0.441 0r 44.1%,which mreans, the independent variables are sense (X1), feel (X2), Think (X3), Act (X4), Relate (X5) and Brand Image (X6)contributes moderately to the dependent variable, Customer Satisfaction (Y).